VOWEL FORMANT VARIABILITY IN THE SPEECH OF PATIENTS WITH DEMENTIA: A PRELIMINARY ANALYSIS (Italiano LinguaDue, 2025)
The phonetic analysis of speech of patients with dementia has mostly involved durational or supra-segmental features, whereas a minor interest has been dedicated to investigating vowel formant variability. To date, the only studies focusing on vowel variations in speakers with dementia are based on a small Japanese dataset. For this reason, we present here a preliminary investigation on 2 Italian-speaking patients diagnosed with dementia compared with control speakers balanced for all sociolinguistic parameters. The descriptive, static and dynamic analysis mixes a quantitative and qualitative approach. The results show a reduction of vowel space in speakers with dementia, especially along the F1 axis. A more stable vowel contour than the control speakers has also been highlighted. In line with the few previous studies on the topic, these results have been explained as a reduction of tongue movement, in particular on the vertical axis, during speech. These preliminary results represent a fundamental starting point for the creation of a larger dataset of analysis, by balancing pathological speakers, with the associated control speakers, with respect to the typology of dementia and its effect on the subject. Variabilità delle formanti vocaliche nel parlato di pazienti con demenza: un’analisi preliminare L’analisi fonetica del parlato di pazienti con demenza ha prevalentemente riguardato tratti di durata o sopra-segmentali, pur se un interesse minore è stato dedicato all’indagine della variabilità delle formanti vocaliche. Allo stato attuale, gli unici studi che si sono concentrati sulla variazione vocalica in parlanti con demenza sono basati su un piccolo dataset giapponese. Per questa ragione, presentiamo qui un’indagine preliminare su 2 pazienti madrelingua italiani diagnosticati con demenza comparati con altrettanti parlanti di controllo bilanciati per tutti i parametri sociolinguistici. L’analisi descrittiva, statica e dinamica combina un approccio quantitativo e qualitativo. I risultati mostrano una riduzione dello spazio vocalico nei soggetti con demenza, specialmente lungo l’asse della F1. Inoltre è stato evidenziato un contorno vocalico più stabile rispetto a quello dei parlanti di controllo. In linea con i pochi precedenti studi su questo argomento, questi risultati sono stati spiegati come una riduzione del movimento della lingua, in particolare lungo l’asse verticale, durante il parlato. Questi risultati preliminari rappresentano un punto di partenza indispensabile per la costituzione di un corpus più ampio di analisi, bilanciando i soggetti patologici, a cui associare i relativi parlanti di controllo, rispetto alla tipologia di demenza e alla sua incidenza sul soggetto.